II Demostración Nacional y los primeros campamentos de verano de la Organización Juvenil (1937-1939) de FET y de las JONS. [II National Demonstration and the first summer camps of the Organización Juvenil (Youth Organization) (1937-1939) of FET y de las JONS]. - Xavier Torrebadella Flix; Eduard Inglés Yuba (Ramón Cantó Alcaraz, 2021)
During the Franco era, summer camps were conceived as the flagships of an ideological mass movement of children and adolescents. The object of this study is to inquire about the link between the II National Demonstration and the first summer camps of the Youth Organization (1937-1939) of FET and JONS. Based on the review of original documentary sources and other research material, a hermeneutical discourse is approached on the underlying message of the Youth Organization in the channelling and domination of childhood and youth. The summer camps are shown to have been used to train up the young generation by grouping inmates in militias and indoctrinating them in discipline, obedience and the sublimation of violence. They went through a system of open-air living to instil them with ideals before moving on into a process to select and indoctrinating fighters for the internal defence of an imagined community: a Spanish nation.